PENGARUH PROMOSI, KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN MENABUNG PADA BANK SUMUT - Berliana Juniscahyanti Zebua Zebua; Melkyory Andronicus (JEBIM Prima, 2021)
The purpose of this research is to analyze how the influence of promotion, service quality, and product quality on the saving decision at Bank Sumut. decrease in customer levels was due to inappropriate promotions, service quality, and product quality. the sample in this research amount to 119 employees. The results of partial hypothesis testing obtained tcount>ttable 3,791 > 1,980 with a significant value of 0.016<0.05, tcount > ttable or 2,301 > 1,980 with a significant value of 0.021 < 0.05, and tcount > ttable or 4.931 > 1.980 with a significant value 0.000 < 0.05. Fcount (10.014) > Ftable (2.45) and significance probability 0.000 < 0.05. The results of the coefficient of determination test obtained the Adjusted R Square value of 0.476, this means 47.6% of the dependent variable, namely the saving decision which can be explained by the independent variables, namely promotion, service quality, and product quality. The conclusion in this research is that partially and simultaneously the variables of promotion, service quality, and product quality have a positive and significant effect on saving decisions at Bank Sumut.